KONSEP ILMU DALAM SHAHIH AL-BUKHARI - Luqman Abdul Jabbar (AT-TURATS, 2016)
Bukhari selected the authenticity of hadith so thoroughly and carefully that he was nicknamed "tabib al-hadis". His intelligence and a strong concern with science was shown in the classification of a separate chapter on the science in his book. Nevertheless Sahih al-Bukhari, as are the books of other hadith collections, has no theoretical-conceptual content of a theory in a mature and clear way. Is still requires help from other disciplines. And the hadits basically requires interpretation, if one wishes to understand it. Keywords: Science, Hadith and Bukhari.